2021
DOI: 10.1111/wre.12517
|View full text |Cite
|
Sign up to set email alerts
|

Functional shifts in weed community composition following adoption of conservation agriculture

Abstract: To better understand the changes in weed communities following the adoption of conservation agriculture (CA), we investigated the functional composition of weed communities in fields implementing CA continuously from 1 to 21 years. Weed surveys were conducted in 100 winter wheat fields of 53 farmers in the Bourgogne‐Franche‐Comté region, Eastern France. Ten response traits were selected to highlight changes in the functional composition of weed communities, using weighted mean value for quantitative traits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Agronomic practices filter weed communities because they impact the internal dynamics of a plant system, changing resource availability, biotic interactions, and habitat stability (Smith & Mortensen, 2017). Correspondingly, trait‐based assessments of weed communities have found that management practices such as tillage (Derrouch et al, 2021; Smith, 2006), fertilizer application (Cordeau et al, 2021; Storkey et al, 2010), and herbicide use (Storkey et al, 2010) filter weed communities. Furthermore, past research has reported that management practices filter weed community traits with differing intensities (Légère et al, 2005; Ryan et al, 2010; Smith & Mortensen, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agronomic practices filter weed communities because they impact the internal dynamics of a plant system, changing resource availability, biotic interactions, and habitat stability (Smith & Mortensen, 2017). Correspondingly, trait‐based assessments of weed communities have found that management practices such as tillage (Derrouch et al, 2021; Smith, 2006), fertilizer application (Cordeau et al, 2021; Storkey et al, 2010), and herbicide use (Storkey et al, 2010) filter weed communities. Furthermore, past research has reported that management practices filter weed community traits with differing intensities (Légère et al, 2005; Ryan et al, 2010; Smith & Mortensen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Functional structure metrics elaborate upon taxonomic diversity by describing changes in plant community trait attributes. A functional approach can elucidate the effects of agronomic practices on weed community composition (Booth & Swanton, 2002) and weed–crop competition (Bennett et al, 2016; Derrouch et al, 2021; Funk & Wolf, 2016; Pakeman et al, 2015). Analysis of functional metrics enables predictions of weed community responses to farm practices across diverse settings because the effect of agricultural practices on species traits is expected to be consistent across different species pools (Booth & Swanton, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…All fields were under CT before the experiment started, and thus had weeds associated to CT. In the long term, conservation agriculture can shift weed communities and reduce weed problems (Derrouch et al, 2021; Fonteyne et al, 2020), which could make manual or mechanical control of weeds more economical, but can also require changes in weed management with the changes in weed species. Our study did not evaluate weed management under ‘full’ conservation agriculture, given the impossibility of practicing crop rotations in the short timeframe, but such rotations have been shown to reduce weeds (Blackshaw, 1994; Fonteyne et al, 2020), although the use of commonly applied herbicides for different crops in the same field over years might have undesirable residual effects (Muoni et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, national and European legislation increasingly call for a drastic reduction in pesticide use, particularly herbicide use (Kudsk and Mathiassen, 2020). Simultaneously, weed diversity is known to be higher in conservation agriculture than in tillage-based systems (Adeux et al, 2019;Derrouch et al, 2021), and weeds support ecosystem services provided by crop auxiliaries or pollinators (Blaix et al, 2018;Barbercheck and Wallace, 2021). So, today's weed management in conservation agriculture must shift from short-term weed control aiming at total eradication to long-term weed management aiming to favor beneficial weed species to the detriment of those damaging crop production, while reducing herbicide use.…”
Section: Introductionmentioning
confidence: 99%